Mitochondrial genome and phylogenetic position of the tawny nurse shark (Nebrius ferrugineus). (2nd January 2017) - Wang, Junjie; Chen, Hao; Lin, Lingling; Ai, Weiming; Chen, Xiao
Abstract: The complete mitochondrial genome of the tawny nurse shark ( Nebrius ferrugineus ) was first presented in this study. It was 16 693 bp in length with the typical gene order in vertebrates. The overall base composition was 33.6% A, 25.6% C, 12.7% G and 28.1% T. Two start (ATG and GTG) and two stop (TAG and TAA/T––) codons were found in the protein-coding genes. The size of 22 tRNA genes ranged from 67 to 75 bp. The origin of L-strand replication could form a hairpin structure. All nodes strongly supported that N. ferrugineus was placed as sister to Rhincodon typus in the Bayesian tree.